Experimental and Numerical Studies on Improving Cyclone Efficiency by Rotation of Cyclone Body - Sayed Saman Salehyar; Ahad Ghaemi; Hossein Mashhadimoslem; Mansour Shirvani (Journal of Chemical and Petroleum Engineering, 2023)
In this study, the separation of silica particles was investigated experimentally and numerically using a cyclone separator. Computational Fluid Dynamics (CFD) simulation was performed using a multi-phase Eulerian-Eulerian model for air-silica powder and a k-ε turbulent model. In the experiments, the effects of operating parameters including silica particle size, airflow rate, and rotational speed on cyclone efficiency were examined. The results showed that by increasing the particle size, the flow rate, and the body speed, the cyclone efficiency enhances. Furthermore, body rotation in the opposite direction of the inlet flow decreases cyclone efficiency by around 48%, and increasing the flow rate and rotation speed increases tangential velocity, resulting in increased centrifugal force and improved cyclone efficiency. The experimental and simulation performance maximums are about 97 percent and 90 percent, respectively. At a constant flow rate and particle size, a 1900 rpm rotating speed of the current direction of inlet flow increases performance by approximately 10-13 percent compared to a stationary body.